2015
DOI: 10.1016/j.healthplace.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Walk Score and Australian adults' home-based walking for transport

Abstract: The relationships of Walk Score, a publicly-accessible walkability assessment tool, with walking for transport to and from home were examined among a large representative sample of Australian adults aged 18-64 years (N=16,944). Residents in highly and somewhat walkable areas were twice and 1.4 times more likely to accumulate 30 min of walking per day compared to those in very car-dependent neighborhoods, respectively. Mean duration of walking was also longer for participants living in highly and somewhat walka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 15 publications
1
47
1
Order By: Relevance
“…Walk Score, a commercially generated index that considers proximities to diverse destinations (e.g., retail, services), provides an estimate of walkability specific to individual addresses and can be obtained for free by entering addresses into a Web site or at cost through arrangements with the company (http://www.walkscore.com). Several studies have demonstrated associations between Walk Score and physical activity obtained by walking, particularly walking for transportation . If submission of addresses to a Web‐based data source is a concern, linkage to precalculated area‐based measures of walkability is an alternative measure.…”
Section: Environmental Constructs and Corresponding Measures Recommenmentioning
confidence: 99%
“…Walk Score, a commercially generated index that considers proximities to diverse destinations (e.g., retail, services), provides an estimate of walkability specific to individual addresses and can be obtained for free by entering addresses into a Web site or at cost through arrangements with the company (http://www.walkscore.com). Several studies have demonstrated associations between Walk Score and physical activity obtained by walking, particularly walking for transportation . If submission of addresses to a Web‐based data source is a concern, linkage to precalculated area‐based measures of walkability is an alternative measure.…”
Section: Environmental Constructs and Corresponding Measures Recommenmentioning
confidence: 99%
“…The highest risks of neoplasms and MI admission rates were found in Kambah (Walk Score 28) and Kaleen (Walk Score 39), which were classified as ‘car-dependent’ by Walk Score. While a number of studies have shown that Walk Score is related to walking for recreation and transportation14–16 37 ours is one of the few studies23 24 that showed a significant relationship between Walk Score and hospital admissions.…”
Section: Discussionmentioning
confidence: 76%
“…Walk Score is a measure of walkability produced by a United States (US)-based company that has been validated37 and has been used in a number of public health studies in the US. In the Australian context, it has been found to have strong relationships with walking for transport in a recent study,14 though relationships with health outcomes have not previously been found 23. Walk Score is a composite measure of destination density.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The built environment around each participant's home was measured using Walk Score. Walk Score has been previously demonstrated as a valid and reliable measure of neighbourhood walkability (Carr et al 2010;Duncan et al 2011;Manaugh and El-Geneidy 2011) and has been used in Australian context (Cole et al 2015). Each participant was assigned a walkability score based on their home address.…”
Section: Data Processingmentioning
confidence: 99%